PENERAPAN PROGRAM PEMBELAJARAN MITIGASI BENCANABAGI SISWA SMP (STUDI KASUS DI SMPN 2 SANDEN) - dan Sri Nuryanto, Wasis Suprapto, Wahyu Yogi Aprilianto, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
The aim of the research was to provide students with the knowledge of how to carry out amitigation earlier through an active, innovative, and fun study.The method was using CD or DVD as the learning media and giving responses before, during, andafter the disaster. The CD included the learning materials such as power point slides and video ofaccidents. The research was a classroom action research conducted by using CD in the middle of thelearning process. The number of the sample was 32.The result of the first meeting of Cycle 1 showed that the score of cognitive aspect was 66.17, thescore of the affective aspect was 45.57, and the score of the psychomotor aspect was 59.25. In thesecond meeting of Cycle 1 the scores increased. The score of cognitive aspect was 77.91, the score of theaffective aspect was 85.15, and the score of the psychomotor aspect was 85.41. Based on the result, itcould be concluded that the use of CD could improve the knowledge of the students of SMPN 2 Sanden.Key words: mitigation accident, CD, students